Islamic financial windows and branches -A study of the essence and legal controls - - Baadji, Abdelatif; Maroua, Khelkhal (The journal of contemporary issues in business and government, 2023)
This study aims to shed light on the Islamic windows and branches, by explaining what is meant by each of the Islamic windows and branches, with a statement of their characteristics and the legal controls that govern these branches and windows developed in conventional banks, as well as addressing the statements of scholars about these windows and branches developed in conventional banks. We have reached a set of results, including that banks resorted to opening windows and Islamic branches to keep the bank's customers from heading towards Islamic banks, as well as the desire of banks to compete with Islamic banks after the successes they have achieved, and the difference between the window and the branch is that the branch is in a building independent of the traditional bank, while the window is inside the traditional bank itself and in the same building, and one of their characteristics is that their transactions are distinguished by the approval of the provisions of Sharia, and a set of The controls issued by the legal Supervisory Board, and the scholars differed in the ruling on dealing with windows and branches between Majiz and opponents, and some of them went to the permissibility of dealing with them for the compelled. Its ruling is linked to the extent to which the legal controls issued by the Commission are applied.